A Wonder Remedy for Prophylaxis, Management and Treatment of Corona Virus Infection- Chyavanprash - Venkataraman, N. Deepak (Current Overview on Pharmaceutical Science Vol. 3, 2023)
COVID- 19 or novel coronavirus infection is a deadly disease which has claimed many lives. COVID-19 actually means coronavirus disease 2019. COVID-19 targets and affects multiple organs like lungs, heart, kidneyetc, thus increasing the mortality and morbidity rates. Allopathic remedies like antivirals, steroids etc., are helpful but are not without side effects. The word Chyavanprash (CP) comprises of ‘Chyawan’ and ‘Prasha’.Chyavan represents ‘degenerative change’ and Prasha symbolises a drug. Since ancient times, the main reasons for consuming CP were to improve immunity and prolong life. CP contains approximately 50 herbs, spices, and minerals, as well as a variety of pharmacological activities on almost all organ systems of the human body. AYUSH is a government organization that works under the Ministry of Ayurveda, Yoga and Naturopathy, Unani, Siddha, and Homoeopathy to promote indigenous alternative medicine systems in India. AYUSH recommends various measures to fight the novel coronavirus infection. Chyavanprash is one such important formulation proposed by AYUSH for COVID-19. The goal of this review is to highlight the constituents and pharmacological activities of CP in the prophylaxis, management, and treatment of COVID-19 by collecting and compiling published research on COVID-19.